Effect of Coolant Inlet Mode on Heat Transfer Characteristics of a Twin-web Turbine Disc Cavity - Y. T. Guo; S. F. Wang; W. J. Shen (Journal of Applied Fluid Mechanics)
Twin-web turbine discs have been the subject of recent research in an effort to lighten the weight of and boost the efficiency of aero engines. This has motivated researchers to investigate other configurations for an expanded blade air supply and twin-web turbine discs. However, the new configuration's cooling mechanism is unclear. In this paper, the flow and heat transfer characteristics of two twin-web turbine disc systems, featuring distinct coolant inlet modes, are investigated through theoretical analysis and numerical simulation. The research results show that the central inlet mode leads to an uneven coolant distribution, a high convective heat transfer coefficient, and a high Nusselt number in the rotor–stator cavity. Meanwhile, the pre-swirl inlet mode improves cooling in the high-temperature region by disturbing the vorticity. Augmenting the dimensionless mass flow rate enhances the cooling efficiency via the notable jet effect, but it also escalates energy loss. As the rotational Reynolds number rises, the entrainment effect of the rotor assumes a dominant role, thereby reducing the swirl ratio. The increased turbulence parameter shifts the primary heat transfer driver from the rotor register to the jet effect, resulting in more uniform temperature changes and a reduced radial inhomogeneity. The pre-swirl inlet mode demonstrates an outstanding cooling performance overall.